Safety issues in construction site of LRT 3 at Section 7 Shah Alam, Selangor / Muhamad Syafiq Suhaimi and An Nisha Nur Welliana Abd Rased - Suhaimi, Muhamad Syafiq; Abd Rased, An Nisha Nur Welliana (2023)
In order to avoid any incidents on a construction site, health and safety regulations must be observed. Because accidents occur on construction sites so frequently, it has also been confirmed that the construction sector is among the most hazardous and dangerous. Since this sector of the economy is one of the most hazardous for employment, all parties, especially the general contractor, must manage and monitor safety. As a result, I choose Section 7 of Shah Alam, Selangor, as my case study location for this essay. Section 7 is the location of the LRT 3 project. This study aims to identify the safety issues at construction sites and rank them in terms of importance. This study employs a quantitative methodology to gather the necessary opinions and viewpoints regarding problems on the construction site and the drawbacks that will occur nearby. Thus, there were 80 respondents in total, and all of them resided nearby the construction site for the purposes of this study. The public's perspective of the LRT 3 construction site in Section 7 Shah Alam, Selangor, is particularly interesting to this study's investigation.